2020
DOI: 10.1002/admi.202000895
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Atomic Layer Deposition of Molybdenum Oxide for Industrial Solar Cells

Abstract: alignment for charge transport. [11] TMOs have work functions ranging from 3 (ZrO 2) to 7 eV (V 2 O 5), making them suitable candidates for energy-level alignment in a variety of devices. [12] In crystalline silicon (c-Si) solar cells, TMOs are being used as transparent, dopant-free heterocontacts to the silicon absorber. [13] These have the potential to replace the heavily doped contacts found in current state-of-the-art heterojunction solar cells, [14,15] which can suffer from parasitic optical absorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…In this novel work Yang et al investigates the possibilities of this technique for Vanadium oxide using it in combination with an amorphous silicon passivating buffer, obtaining outstanding devices up to 21.6% efficiencies. Other attempts to fabricate operative photovoltaic devices with ALD deposited TMOs have not been as successful 35,36 indicating how ALD deposition of Transition Metal Oxides is not an easy task. The explored solar cell architecture by Yang et al does not take advantage of the reported TMO enhancement in optical properties with respect to the conventional heterojunction structure using amorphous silicon 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In this novel work Yang et al investigates the possibilities of this technique for Vanadium oxide using it in combination with an amorphous silicon passivating buffer, obtaining outstanding devices up to 21.6% efficiencies. Other attempts to fabricate operative photovoltaic devices with ALD deposited TMOs have not been as successful 35,36 indicating how ALD deposition of Transition Metal Oxides is not an easy task. The explored solar cell architecture by Yang et al does not take advantage of the reported TMO enhancement in optical properties with respect to the conventional heterojunction structure using amorphous silicon 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Transparent semiconducting metal-oxides have become the foundation of devices such as thin-film transistors (TFTs), solar cells, photodetectors, and memories. [1][2][3][4] The majority of these devices rely on n-type semiconducting compounds (e.g., InGaZnO, InZnO, ZnSnO, and ZnO), for which materials and processes are well established. In contrast, the development of reliable and high performance p-type oxide materials has proven itself to be challenging owing to their inherently high density of interfacial defect states and comparably poor electrical performance, [5] which in turn hampers the effective spatial separation of precursor and coreactant, i.e., the substrate moves underneath injector heads from which either precursor or coreactant are continuously flowing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 256 ] In recent times, SALD has also been employed to deposit materials for various applications such as ZnO in thin film Li‐ion batteries, [ 257 ] SnO x in perovskite solar cell, [ 258 ] Al 2 O 3 as moisture barrier coating, [ 259 ] and MoO x as charge selective layer in Si solar cell. [ 260 ] Similarly, close‐proximity SALD has been employed commercially by companies such as Levitech and SoLayTec to deposit Al 2 O 3 thin films on Si solar cells for surface passivation. To date, high throughput SALD have mainly been limited to few materials such as ZnO, Al 2 O 3 , TiO 2 .…”
Section: Emerging Technologiesmentioning
confidence: 99%